Hubungan Persepsi dengan Kualitas Hidup Pasien Hipertensi Lanjut Usia di RSUD Sultan Syarif Mohamad Alkadrie Pontianak - Nabilla Putri Pratiwi; Eka Kartika Untari; Robiyanto Robiyanto (Faculty of Pharmacy, Universitas Gadjah Mada)
Hypertension is still a health problem for the elderly group. The misperception about hypertension still occurs to the elderly. They often ignore hypertension and it impact their quality of life. The aim of this study is to obtain patient perceptions and the elderly’s quality of life who are experiencing hypertension, also the relationship between patient perceptions and the elderly’s quality of life who are experiencing hypertension at Sultan Syarif Mohamad Alkadrie Hospital Pontianak. This study was observational with analytival survey design. EQ-5D-3L (EuroQol five dimensions and B-IPQ (Brief Illness Perception Questionnaire) Indonesian version are instruments used which were valid and reliable. The subjects were hypertensive outpatient attending Sultan Syarif Mohamad Alkadrie Hospital Pontianak at aged> 60 years. The sample size was 118 respondents which were obtained from purposive technique sampling. Data was collected through B-IPQ instruments to measure patient perceptions, and EQ-5D-3L to measure patients' quality of life. The relationship between perception and quality of life was analyzed using Fisher's Exact Test with a 95% confidence level (α = 0.05). The results showed the percentage of respondents who had a positive perception was 74.22%, and good quality of life was 76.56%. The results of statistical analysis show there is a significant relationship between patient perceptions and the quality of life of elderly patients who experience hypertension at Sultan Syarif Mohamad Alkadrie Hospital Pontianak with value of p = 0,000.